No Own-Age Advantage in Children's Recognition of Emotion on Prototypical Faces of Different Ages. - Sarah Griffiths; Ian S Penton-Voak; Chris Jarrold; Marcus R Munafò (PLoS ONE)
We test whether there is an own-age advantage in emotion recognition using prototypical younger child, older child and adult faces displaying emotional expressions. Prototypes were created by averaging photographs of individuals from 6 different age and sex categories (male 5-8 years, male 9-12 years, female 5-8 years, female 9-12 years, adult male and adult female), each posing 6 basic emotional expressions. In the study 5-8 year old children (n = 33), 9-13 year old children (n = 70) and adults (n = 92) labelled these expression prototypes in a 6-alternative forced-choice task. There was no evidence that children or adults recognised expressions better on faces from their own age group. Instead, child facial expression prototypes were recognised as accurately as adult expression prototypes by all age groups. This suggests there is no substantial own-age advantage in children's emotion recognition.